Evaluation of Psychosocial Outcomes of Living Liver Donors in Liver Transplantation - Sarıgöl Ordin, Yaprak; Harmancı Seren, Arzu Kader; Karayurt, Özgül; Aksu Kul, Gülay; Kılıç, Murat; Bozoklar, Cemal Ata; Tokat, Yaman (Turkish Journal of Gastroenterology, 2022)
Background: The purpose of this study was to evaluate the risk factors affecting psychosocial outcomes of living liver donors after liver transplantations. Methods: This was a descriptive, cross-sectional study. The sample consisted of living liver donors followed by 2 liver transplantation centers in 2 private hospitals in 2 different provinces, between August 2017 and October 2019. All the living liver donors were contacted without a time frame after donation and all the participants were evaluated once. The Beck Depression Scale, SF-36, General SelfEfficacy Scale, and Perceived Available Support Scale were used to collect data. The t-test, Kruskal–Wallis test, Mann–Whitney U-test, and Pearson correlation analysis were used for data analysis. Results: The mean age of the patients was 34.31 ± 8.22 years. There was a positive, weak correlation between age and physical function. Gender, marital status, financial status, and education levels significantly affected physical components, social function, vitality, depression, and self-efficacy scores. High depression levels negatively affected the physical component, self-efficacy, and social support scores of the living liver donors. High self-efficacy positively affected social support. Conclusion: The study revealed that gender, marital status, employment status, and education levels were associated with psychosocial outcomes. The financial status was the main factor affecting each psychosocial variable. Financial status needs to be assessed in detail before and after the operation.